2019
DOI: 10.4103/jpbs.jpbs_2_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries and periodontal status among Down’s syndrome population in Riyadh City

Abstract: Aim: Aim of the present study was to evaluate the prevalence of dental caries and periodontal status among Down’s syndrome population in Riyadh City. Materials and Methods: A total of 81 male Down’s syndrome subjects were examined in this study. All subjects were recruited from the Saudi Center for Down Syndrome, Riyadh. Clinical examination was carried out by a single precalibrated examiner. Dental caries experience was counted according to the DMFT (decayed, missing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 9 publications
1
14
0
2
Order By: Relevance
“…Of these, 15 articles were excluded and are listed in Supplementary Table S1 , along with the reasons for their exclusion ( Supplementary Table S1 ). Therefore, 38 studies were included in this review [ 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. No additional studies were found upon hand searching or searching the gray literature.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 15 articles were excluded and are listed in Supplementary Table S1 , along with the reasons for their exclusion ( Supplementary Table S1 ). Therefore, 38 studies were included in this review [ 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. No additional studies were found upon hand searching or searching the gray literature.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Thirty-five studies were cross-sectional [ 10 , 11 , 12 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 46 , 47 , 48 , 50 , 51 ], one was a longitudinal study [ 45 ], and two were retrospective studies [ 28 , 49 ]. Twenty-two studies were conducted in or near Riyadh [ 10 , 11 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 26 , 27 , 28 , 29 , 32 , 33 , 34 , 35 , 38 ...…”
Section: General Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Se ha reportado una baja prevalencia de caries en pacientes con SD en muchos países 17,18 . Sin embargo, es contradictorio que algunos reportes sobre el estado de salud bucal en estos pacientes han señalado una alta prevalencia de caries dental 19 . El presente estudio encontró una elevada prevalencia entre los sujetos evaluados.…”
Section: Discussionunclassified